Design and modeling of energy generated magneto rheological damper - Ahamed, Raju; Rashid, Muhammad Mahbubur; Firdaus, Md Meftahul; Md. Yusof, Hazlina (Korean Society of Rheology, Australian Society of Rheology, 2016)
In this paper an energy generated mono tube MR damper model has been developed for vehicle suspension systems. A 3D model of energy generated MR damper is developed in Solid Works electromagnetic simulator (EMS) where it is analyzed extensively by finite element method. This dynamic simulation clearly illustrates the power generation ability of the damper. Two magnetic fields are induced inside this damper. One is in the outer coil of the power generator and another is in the piston head coils. The complete magnetic isolation between these two fields is accomplished here, which can be seen in the finite element analysis. The induced magnetic flux densities, magnetic field intensities of this damper are analyzed for characterizing the damper’s power generation ability. Finally, the proposed MR damper’s energy generation ability was studied experimentally.